Ordem econômica: aperfeiçoamento e evolução nas constituições brasileiras de 1824 a 1988 - Silva, Nicholas Takamoto Leal da (2021)
The present paper aims to demonstrate, through an extensive bibliographical research, the evolution of the Economic Order in all the Constitutions that have ever existed in Brazil, demonstrating innovations and similarities that they may have had between them. It should be noted that not all of them had a dedicated space within the Constitution that specifically directed the economy, often motivated by the historical and political context in which they would be inserted, which would explain the lack of zeal with the Economic Order in that period. However, for the analysis of each Constitution, there is a necessary path that needed to be traversed in advance for a full understanding of it, therefore, in light of the general theory of the State, and prioritizing the intrinsic approach between the political-economic relationship and its evolution throughout from history, themes such as: the origin of the State and its foundations will be elucidated: economic, sociological and legal (jusnaturalist and juspositivist doctrines); economic systems, Constitutionalism and the Economic Order since the beginning, so that the evolution of the Economic Order in Brazil could be clarified and substantiated. It is important to note that there are several factors that led to the evolution of this theme on the national scene, but the most relevant were the European and North American influences, highlighting that the Constitution of Weimar (1919) would have been the first major influence in the constitution of the Order Economic in national territory. Given the above, it can be interpreted that the Magna Cartas of 1824 and 1891 mention little about the subject, with the first being based on political and individual rights (art.178), and the second mentioning a possible economic intervention through norms infraconstitutional. So the great watershed would be the Constitution of 1934, influenced by the innovations brought by the Constitution of Weimar (1919), incorporating concepts of the social rule of law, inserting rules on the Economic Order. These concepts brought by the 1934 Constitution were so innovative that they remained virtually unchanged in the 1937 and 1946 constitutions, including in the latter the search for national development, which was followed by the 1967 Constitution, and later by Amendment No. 1 of 1969, which practically did not change the 1967 Constitution in relation to the content of the Economic Order. Finally, the Constitution of 1988, currently in force, has a modern and interesting Economic Order, bringing in its essence the concern for the dignity of the human person, which made even the Economic Order be interpreted in light of the fundamental precepts constitutional, transforming the economy into an important instrument of national socioeconomic development, therefore, intervening through legal instruments when strictly necessary, in order to preserve fundamental precepts, such as free enterprise.